Poverty, Inequality and Policy 2017
DOI: 10.5772/intechopen.68581
|View full text |Cite
|
Sign up to set email alerts
|

Growing up in Rural vs. Urban Poverty: Contextual, Academic, and Cognitive Differences

Abstract: This chapter aims synthesize current literature and research from a variety of ields to highlight what we know about the (1) contextual, (2) academic, and (3) cognitive diferences between children growing up in urban versus rural poverty. The goal is to understand the unique needs of children growing up in urban and rural poverty to, in turn, place us in a beter position to efectively remediate through targeted interventions and policy change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…Interestingly, we neither find a relation between processing speed and the other individual nor socioenvironmental variables. This result disagree with previous studies that showed a relation between these factors and cognitive performance: parental education (Foulkes & Mori, ; Mykerezi et al, ; Tine, ), father's occupation and overcrowding (Ngure et al, ) as well as past preschool attendance (Castro & Rolleston, ; Gouin et al, ) have been associated with rural child cognitive achievement. In fact, our results suggested an effect of SES (linked with socioenvironmental variables) since these children obtained a mean processing speed performance lower than expected for their age.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, we neither find a relation between processing speed and the other individual nor socioenvironmental variables. This result disagree with previous studies that showed a relation between these factors and cognitive performance: parental education (Foulkes & Mori, ; Mykerezi et al, ; Tine, ), father's occupation and overcrowding (Ngure et al, ) as well as past preschool attendance (Castro & Rolleston, ; Gouin et al, ) have been associated with rural child cognitive achievement. In fact, our results suggested an effect of SES (linked with socioenvironmental variables) since these children obtained a mean processing speed performance lower than expected for their age.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies used general cognitive development test (e.g. Gouin et al, ; Mykerezi et al, ; Ngure et al, ); others used specific skills tests—different from processing speed (Tine, ) and a final group of studies created a measure by combining other measures of cognitive achievement (Castro & Rolleston, ; Foulkes & Mori, ). Thus, our results could not find significant differences, unlike other studies which did find them, probably due to the cognitive measure used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current work documents a more complete cognitive profile of the two populations by determining that individuals from rural and urban poverty also have distinct inhibition abilities, but not language or incidental memory abilities. Taken together, these two general sets of findings improve our understanding of the cognitive development of individuals growing up in rural poverty-a growing, but underrepresented population (Lichter & Schafft, 2016;Murphy, 2007;Tine, 2017).…”
Section: Discussionmentioning
confidence: 84%